A Sample Survey of the Commission on Money and Credit Research Papers - Bronfenbrenner, Martin (The Review of Economics and Statistics, 1963)
T HE Commission on Money and Credit has laid its 285-page egg 1 and gone over like a lead balloon -choose your own metaphor with both the economists and the general public. Certain of its administrative suggestions, notably those involving reconstitution of the Federal Reserve System's Board of Governors, have attracted a significant modicum of attention.2 On the substantive side, however, the Commission's main body of work appears already spurlos versen,kt, in unhappy contrast with both the National Monetary Commission of fifty years past, whose influence it was intended to rival, and the Radcliffe Report of I959,3 its closest contemporary transatlantic equivalent. This unhappy fate rather befits a series of attempted least common denominators between unreconciled and possibly unreconcilable special interests, which turned out to be meaningless verbal compromises as often as anything more. Indeed, the least uninteresting feature of the report to this reader was the triangular running battle between the predominantly sound don't rock the boat position of its text and the two accompanying sets of mutually contradictory footnote dissents. Set i, contributed primarily by the labor bloc (Lubin, Nathan, Rieve, Ruttenberg, and Thorp, with Ruttenberg the principal spokesman), stands for guaranteed full employment and a 5 per cent annual growth rate, at any cost in direct controls over everyone but organized labor, and over everything but wages. Set 2, contributed by a mixed bag of business, finance, and agricultural4 spokesmen (Black, Lazarus, Miller, Schwulst, Shuman, Thomson, and Yntema) stands for Free Enterprise in the economic aggregates -McKinley minus the gold standard.5 Rather than aim a supernumerary nail at the Commission's coffin, I propose to examine a biased sample of the professional papers submitted for the Commission's use, and to all appearances neglected by the Commission in favor of cliches and weasel words masquerading as common sense.6 The papers are to an econo-